Effectiveness of a multimodal intervention in promoting physical activity among sedentary elderly population in socially and economically constrained settings - A quasi-experimental study - Jyothi Vasudevan; Lalithambigai Chellamuthu; RS Swarnalatha; Meena Ramanathan (Journal of Family Medicine and Primary Care)
Introduction: Aging is becoming a major challenge for policymakers. Regular exercise helps keep elderly people mobile, enhances physical and mental abilities, and to some extent delays the effects of chronic illnesses. Objectives: To evaluate the effectiveness of a multimodal intervention to increase physical activity levels among sedentary elderly living in socially and economically constrained settings. Materials and Methods: A quasi-experimental study was conducted in selected old age homes in Puducherry, South India in 2022 for 3 months. Individuals aged ≥60 years, both genders residing in selected old-age homes were included through convenience sampling. The sample size was 36 subjects per arm [three arms namely E1, E2 (intervention arms), and C (control arm)]. Baseline data collection on physical activity was collected using a semi-structured questionnaire in all three arms. The intervention arms (E1 and E2) received a multimodal intervention to promote physical activity. In addition, E1 arms were instructed to perform exercises with an “exercise partner” and to maintain a daily log. At the end of 8 weeks, follow-up data collection was done using the same questionnaire in all three arms. Data entry was done by MS Excel 2010 and analysis using SPSS version 21. Results: The mean (SD) of the days of physical activity per week and time of physical activity per day before and after the intervention among E1 and E2 were compared using paired t-tests. The difference between pre- and post-intervention was found to be statistically significant, that is, P value <0.05 in both the groups, thereby proving the effectiveness of the intervention. The difference between the three groups was found to be statistically significant, that is, P value <0.05. Conclusion: This multimodal intervention is found to be effective in increasing the physical activity of the participants in the interventional arms. Furthermore, having an exercise partner was found to be beneficial in ensuring motivation and compliance to carry out physical activity among the elderly living in socially and economically constrained settings.